UPAYA PENINGKATAN TRANSPARANSI DALAM PENYELENGGARAN PEMILU DI TINGKAT DESA DI DESA CIJERUK KECAMATAN MEKAR BARU KABUPATEN TANGERANG - Fajri, Adi Nur; Bintang, Nofani Wildania; Puspa, Rani; Fatoni, Malik (Yayasan Education and Social Center, 2024)
The purpose of holding a community service program (PKM) in the field of village government, in Cijeruk village with the title Efforts to Increase Transparency in the Implementation of Elections at the Village Level. This community service activity aims to convey knowledge about the implementation of transparency in the general election process (election) in Cijeruk Village. The main theme of this activity is how to increase transparency in the implementation of elections at the village level. The formulation of the problem faced is how the people of Cijeruk Village can monitor the course of the election in a transparent and effective manner. The purpose of this activity is to increase public awareness and participation in monitoring the election process using effective transparency methods. The socialization participants of this activity are residents of Cijeruk Village consisting of various levels of society. This activity involves the delivery of material on the importance of transparency in elections, as well as practical training on how the public can monitor the course of the election transparently. The result of this activity is an increase in awareness and participation of the Cijeruk Village community in monitoring the election process using effective transparency methods